(untitled) (Revista de Ciências Agroveterinárias, 2023)
ABSTRACT The association of conventional fertilizers with fertilizers of organic origin is a well-known practice in agriculture for achieving high productivity and also with the adoption of inoculants, composed of bacteria for promoting better plant development of crops. Thus, the objective of the work was to investigate the growth and productivity of radish with organic fertilization and the influence of the use of nitrogen fixing bacteria of the genus Azospirillum spp. radish (Raphanus sativus L.) Hybrid Margaret Queen. The treatments were the use of different doses of organic fertilizer and the application of Azospirillum brasilense, besides the control. At the end of the cycle, plant height, tuber diameter, tuber fresh mass, tuber dry mass, and total tuber fresh mass were evaluated. With and without application of A. brasilense, increases of 16.5% and 6.40% in tuber diameter were obtained, respectively. Without application of A. brasilense, there was an increase of 0.37% in leaf dry mass when the maximum concentration of 8 kg m² of organic fertilizer was used. For root fresh mass and root dry mass, with foliar application of A. brasilense, there was an increase of 9.57% and 0.67%, while without A. brasilense there was an increase of 2.43% and 0.22%. There were increases of 12.83% for total fresh mass with the management of A. brasilense and 3.4% without A. brasilense, using the maximum concentration of 8 kg m² of organic fertilizer. For height, there was an increase of 5.12% without A. brasilense. It was concluded that organic fertilization alone or combined with A. brasilense is an alternative in radish production. KEYWORDS: Raphanus sativus L; organic fertilization; Productivity; Vegetables.